Inspecting the Merit System's "Pivotal Idea": Does Competitive Examination Increase the Qualifications and Quality of the U.S. Federal Service?. (June 2020) - Johnson, Tim; Lewis, Gregory B.
According to its designers, the U.S. merit system centered on a "pivotal idea": The civil service would use "open, fair, honest, impartial, competitive examination" to find the people "best fitted to discharge the duties of the position." Officials would announce job openings to the widest-possible applicant pool and assess that pool on uniformly applied, job-relevant criteria. Over time, however, alternative hiring mechanisms have increased in popularity as means to improve the speed or flexibility the hiring process, with limited research on their impact on the federal service. To understand their effects, we examine all federal, nondefense employees hired between 1983 and 2013 to assess whether four alternative hiring procedures affect the educational attainment (a proxy for qualifications) and career advancement (a proxy for quality) of new hires. We find that employees hired through competitive examinations possess more education upon entry than employees selected through two of those alternative procedures; however, employees hired through all four alternative procedures advance in their careers at least as rapidly as those selected via competitive examinations.